A new soldier beetle of the extinct tribe Cacomorphocerini Fanti & Kupryjanowicz, 2018 - Fanti, Fabrizio; Pankowski, Mary K. (Zootaxa, 2019)
A new fossil Cacomorphocerus Schaufuss, 1892 from Baltic amber, i.e., Cacomorphocerus coleae sp. nov. is described. Related to C. eocenicus Bukejs, Fanti & McKellar, 2019, the new species is characterized by 12 antennomeres that are little modified, with antennomere VI saucer-shaped and asymmetrical, antennomere V enlarged and antennomeres VII and VIII squarish and sub-rectangular. The slightly modified antennae of some species of Cacomorphocerus confirm a relationship with the genus Sucinorhagonycha Kuśka, 1996. Therefore, given the synapomorphy of the antennae, Sucinorhagonycha is transferred from the tribe Cantharini Imhoff, 1856 to Cacomorphocerini Fanti & Kupryjanowicz, 2018 (new placement).